Exile and Migration in the APCLAI Archive - Luque, Rocío (Oltreoceano - Rivista sulle migrazioni, 2024)
This work presents the film material from the “Centro Audiovisivo Latino Americano” (CALA) Archive of the “Associazione per la Promozione della Cultura Latino Americana in Italia” (APCLAI) that focuses on exile and other forms of migration, with the aim of offering an overview of the wide variety of migratory routes affecting the Latin American region: the Great Italian migration to the Americas that began in the last decades of the 19th century and continued until the First World War; the flight of Jews from the pogroms during the forty years between 1881 and 1921; the displacements as a result of political persecution by authoritarian regimes that spread across Europe after the First World War; the destierro of thousands of Spaniards during the Civil War and after the establishment of the Franco regime; the flight of Jewish victims of Nazism; the European migration between the end of the Second World War and the 1970s; the exile of Latin Americans to the United States or Europe, driven by the different regimes that followed in the second half of the 20th century; and the crossing of the “Grande Frontera Norte” between Mexico and the United States and, for those from Central America, the equally cruel southern border of the Mexican State. The aim, starting from this general framework, is to understand the view that Latin American cinematography gives us on the theme of migration and, specifically, on that form of forced migration that constitutes exile, while giving visibility to this extremely valuable artistic medium that has yet to receive due recognition, on a par with Latin American literature.